Restitution as a Requirement for the Implementation of Restorative Justice Against General Crimes Related to Property - Muwardi, Ardito; Surono, Agus; Nugroho, Hibnu (KnE Social Sciences, 2023)
Restitution is a monetary remedy paid by a perpetrator or a third party to a victim or their family. It can be implemented by returning property, payment for losses or suffering, or reimbursement of costs. However, restitution is not applicable to all types of crimes; thus, not all victims have access to it.The issue of legal protection for victims is still an ongoing discourse, and many parties believe that its implementation is still far from perfect and in need of legal reform due to the inability of the perpetrators to pay restitution to the victims. This study uses qualitative methods by examining secondary data such as documents, laws and regulations, scientific findings, and books. This study finds that the application of restorative justice in criminal cases, especially property crimes provides certain flexibility for the community to search for a settlement. The perpetrator paying for restitution is an absolute requirement for restorative justice in settlement of property-related crime as an alternative to the conventional court proceeding. Moreover, the perpetrators, victims, and the community can all be involved in a discussion process to reach a consensus regarding a solution to a conflict avoiding harming any parties, for instance, a settlement without punishment. Keywords: restitution, restorative justice, criminal act, property